Natural gas : a basic handbook - Speight, James G. (Gulf Pub. Co., 2007)
Natural gas represents nearly one-quarter of the world's energy resources. More than half of American homes rely on it as their main heating fuel. It serves as the raw material necessary in everyday paints, plastics, medicines and explosives. It produces the cleanest of all fossil fuels. It is natural gas-and everybody should acquire a basic understanding of it. This valuable easy-to-use reference supplies all the basics that every person should know about the natural gas industry. Introductory engineers, managers and analysts will benefit from this informative, practical handbook. Natural gas remains a vital component of all energy sources, and with an increasing demand for information on this useful energy source, Natural Gas: A Basic Handbook is an essential tool for anyone involved in the energy industry.